2011
DOI: 10.4025/actasciagron.v33i4.8629
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the wood-borer and the factors affecting its attack on Caryocar brasiliense trees in the Brazilian Savanna

Abstract: ABSTRACT. The objectives of this work were to identify the wood-borer of the trunk of Caryocar brasiliense Camb. (Caryocaraceae) and the effects of tree size, chemical and physical soil attributes, and floristic diversity in its attack. The wood-boring caterpillar of the trunck of C. brasiliense belongs to the family Cossidae (Lepidoptera). The number of pupae and the amount of sawdust produced by the wood-borer per tree was higher in the pasture 1 of Montes Claros and pasture in Ibiracatu than in the other fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…(Malpighiales: Caryocaraceae) is a flag species of the Cerrado, presents wide distribution (Brandão & Gavilanes 1992;Bridgewater et al 2004;Leite et al 2006a) and can reach up to 10 m high while the canopy may reach 6 m wide (Leite et al 2006a(Leite et al , 2011a(Leite et al , 2012a. The leaves of C. brasiliense are alternate, trifoliate and have high trichome density; the flowers are hermaphrodite but mostly cross pollinated.…”
mentioning
confidence: 99%
“…(Malpighiales: Caryocaraceae) is a flag species of the Cerrado, presents wide distribution (Brandão & Gavilanes 1992;Bridgewater et al 2004;Leite et al 2006a) and can reach up to 10 m high while the canopy may reach 6 m wide (Leite et al 2006a(Leite et al , 2011a(Leite et al , 2012a. The leaves of C. brasiliense are alternate, trifoliate and have high trichome density; the flowers are hermaphrodite but mostly cross pollinated.…”
mentioning
confidence: 99%
“…The higher numbers of E. rufomarginata were observed on the C. brasiliense trees that had the largest canopies. The larger C. brasiliense trees had more food resources than other trees did for insects to increase diversity and abundance, as was observed for woodborers (Lepidoptera: Cossidae) and populations of defoliators (Coleoptera and Lepidoptera) (Leite et al, 2011d;2012c;.…”
Section: Resultsmentioning
confidence: 67%
“…Similary, Leite et al (2006) observed more production of C. brasiliense fruits for the pasture trees (biggest trees) than for the trees on the cerrado (smallest trees) in Montes Claros, Minas Gerais State. Moreover, the farmers left forest reserves in areas with soils with poor physical structure (sandy or rocky) in the cerrado in the north of Minas Gerais State, Brazil which reduced production and the natural regeneration of C. brasiliense (Leite et al, 2006(Leite et al, , 2011d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…: Family : Species (References) Lepidoptera: Blastobastidae: Platinota rostrata Lepidoptera: n.i. (CA RREGA RO et al, 2009) Lepidoptera: Cossidae: n.i (LEITE et al, 2011). Lepidoptera: Gelechiidae: n.i (CARREGA RO et al, 2009).…”
unclassified